Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/sms.12547
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of elite high‐altitude climbers

Abstract: Factors underlying the amplitude of exercise performance reduction at altitude and the development of high-altitude illnesses are not completely understood. To better describe these mechanisms, we assessed cardiorespiratory and tissue oxygenation responses to hypoxia in elite high-altitude climbers. Eleven high-altitude climbers were matched with 11 non-climber trained controls according to gender, age, and fitness level (maximal oxygen consumption, VO2 max ). Subjects performed two maximal incremental cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(71 reference statements)
1
13
0
Order By: Relevance
“…Bernardi et al (2006) reported that successful high altitude climbers, who could reach the highest summits without oxygen, were characterised by a lower ventilatory sensitivity to hypoxia and a slower ƒ R , compared to those who did not succeed or needed supplemental oxygen. These findings were supported by Puthon et al (2016) who reported that ƒ R was larger in control participants Breathing frequency (% increase from baseline) Tidal Volume (% increase from baseline) compared with elite high-altitude climbers, while V T was larger in climbers compared with controls during maximal incremental cycling tests in both normoxic and hypoxic conditions. Schoene et al (1984) have previously demonstrated that the drop in arterial oxygen saturation that occurs with exercise at altitude is inversely related to HVR, and sojourners with high HVR may perform better at extreme altitude.…”
Section: Results: Ventilatory Responsessupporting
confidence: 71%
See 2 more Smart Citations
“…Bernardi et al (2006) reported that successful high altitude climbers, who could reach the highest summits without oxygen, were characterised by a lower ventilatory sensitivity to hypoxia and a slower ƒ R , compared to those who did not succeed or needed supplemental oxygen. These findings were supported by Puthon et al (2016) who reported that ƒ R was larger in control participants Breathing frequency (% increase from baseline) Tidal Volume (% increase from baseline) compared with elite high-altitude climbers, while V T was larger in climbers compared with controls during maximal incremental cycling tests in both normoxic and hypoxic conditions. Schoene et al (1984) have previously demonstrated that the drop in arterial oxygen saturation that occurs with exercise at altitude is inversely related to HVR, and sojourners with high HVR may perform better at extreme altitude.…”
Section: Results: Ventilatory Responsessupporting
confidence: 71%
“…These findings were supported by Puthon et al . () who reported that ƒ R was larger in control participants compared with elite high‐altitude climbers, while V T was larger in climbers compared with controls during maximal incremental cycling tests in both normoxic and hypoxic conditions.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The hypoxic ventilatory (absolute or relative to body weight) and cardiac responses during the exercise test (at rest, 25%N, 50%N, Exh H and at 90 W) were calculated as follows Puthon et al 2016):…”
Section: Discussionmentioning
confidence: 99%
“…The hypercapnic ventilatory and cardiac responses during the resting hypercapnic response test were calculated as follows Puthon et al 2016):…”
Section: Discussionmentioning
confidence: 99%